Answer: (a) e ^ -3x (b)e^-3x
Step-by-step explanation:
I suggest the equation is:
d/dx[integral (e^-3t) dt
First we integrate e^-3tdt
Integral(e ^ -3t dt) as shown in attachment and then we differentiate the result as shown in the attachment.
(b) to differentiate the integral let x = t, and substitute into the expression.
Therefore dx = dt
Hence, d/dx[integral (e ^-3x dx)] = e^-3x
Answer:
She is wrong. She would have walked 337 miles after 29 weeks.
Step-by-step explanation:
13x29=337
The total number of rose bushes in the two gardens is 26.
Answer:
<u>=-2y</u>
Step-by-step explanation:
y-3y
<u>=-2y</u>